Predictive value of left atrial strain in relation to atrial fibrillation following acute myocardial infarction. (1st October 2022) - Svartstein, Anne-Sophie Winther; Lassen, Mats Højbjerg; Skaarup, Kristoffer Grundtvig; Grove, Gabriela Lladó; Vyff, Frederikke; Ravnkilde, Kirstine; Pedersen, Sune; Galatius, Søren; Modin, Daniel; Biering-Sørensen, Tor
Abstract: Background: Atrial fibrillation (AF) is the most common arrythmia following ST-segment elevation myocardial infarction (STEMI) and can lead to stroke and other heart-related diseases. This study aimed to determine the prognostic value of left atrial (LA) strain, obtained by speckle tracking echocardiography (STE), in predicting incident AF outcomes following STEMI treated with primary percutaneous coronary intervention (pPCI). Methods and results: This prospective study comprised of 392 STEMI patients treated with pPCI. The patients had an echocardiography performed at a median of two days after their STEMI. Along with conventional measures, LA strain was obtained by speckle tracking from two apical projections. The outcome was new-onset atrial fibrillation. LA reservoir, contractile and conduit strain were measurable from echocardiograms of 303 included patients. At a median follow-up time of 5.6 years (IQR: 5.0–6.1 years), 18 patients (6, 3%) developed incident AF. Mean age was 62.0 years ±11.5 and follow-up was 100%. Significantly lower LA strain values were observed in patients who experienced AF during follow-up as compared to patients who didn't. Both reservoir, contractile and conduit strain were significant univariable predictors. In the multivariable model, only LA reservoir strain remained a significant independent predictor of AF. Conclusion: Left atrial reservoir strain obtained by two-dimensional speckle tracking echocardiography is an independent predictor of incident AF following STEMI. Highlights: Prognostic value of left atrial strain obtained by speckle tracking echocardiography. Prognostic value of strain on atrial fibrillation following myocardial infarction. Significantly lower left atrial strain in patient with atrial fibrillation. Left atrial reservoir strain is a significant predictor of atrial fibrillation.